Podstawy Teorii Plastycznego Płynięcia Ciał Dyskretyzowanych - Kleiber, M. (Engineering Transactions, 1973)
The paper formulates the foundations of the theory of plastic flow of discretized bodies. Under the notion of a discretized body we understand an approximate model of continuous media derived in the process of discretization. The solution of the problem of the load carrying capacity of two types of plane gridworks serves as an example of application of the theory.